Korektivne osteotomije v zdravljenju haluks valgusa - Rečnik, Gregor (Medicinski razgledi, 2006)
Hallux valgus is a deformity without a known cause. Failure of conservative treatment is an indication for operative correction. First metatarsal osteotomy is the basis for over 130 different procedures. None of them is universally applicable for all deformities and many of them have serious shortcomings. The classical Mitchell osteotomy does not ensure correction options have made the Scarf osteotomy interesting to many surgeons nowdays. Osteotomy of neighbouring bones is widening the deformity indications and improving the quality of the above mentioned procedures.
Keywords: Hallux Valgus; Kirurgija; Osteotomija; surgery; Haluks valgus; Metode; therapy; zdravljenje; Osteotomy; methods